«Io ho bisogno di animali teatrali»: Giorgio Strehler e la recitazione nel teatro d’opera - Paoletti, Matteo (Mimesis Journal, 2018)
«It is not enough that they sing well [...]. I need theatrical animals». So, Giorgio Strehler, in 1997, gave indications to the musicologist Carlo de Incontrera for the distribution of Così fan tutte, a production that in his own mind should have marked the crossing of the boundaries between straight and opera theater, by creating in the new headquarters of the Piccolo Teatro the «lyric theater of art» he had been pursuing for a large part of his career. Although Strehler dies after only eleven days of rehearsal, the production is crucial for rethinking the relationship between the director and the opera theatre: at the very end of his career, Strehler is finally inspired by the models of the German Regietheater and in particular by Felsenstein’s work, which he aims to adapt in “his” Piccolo Teatro. The research develops from the rich and unpublished private correspondence between Strehler and Carlo de Incontrera, courtesy of the musicologist.